"...ikke Gud, men hans engle..." - Om metode i Giorgio Agambens 'The kingdom and the glory' - Eggers, Nicolai von (Slagmark - Tidsskrift for idéhistorie, 2018)
In this article I investigate the methodological experiments Italian philosopher Giorgio Agamben’s performs in his book The kingdom and the glory, which is a part of his larger project on ‘homo sacer’. Method is here taken in its widest sense from philosophical considerations on how to write history and what one can argue with it, to the techniques and strategies, almost tricks, Agamben uses to make history speak and philosophize. That is, I am not as much interested in what Agamben’s argument is, as in how his arguments are put forward. I focus on three such methods in The kingdom and the glory: Political topicality or contemporary political-philosophical critique; defunct discussions of methodology, e.g. discussions of political theology in Germany 1950-1980; and archeology and genealogy as interrelated approaches. More generally, I argue that Agamben’s works and his methods are an important contribution to the way in which one can do research as a historian of ideas.